Supporting social interaction for older users in game-like 3D virtual worlds - Zaphiris, Panayiotis; Siriaraya, Panote; Siang Ang, Chee (My University, 2013)
There has been ongoing research into how 3D virtual worlds can be designed to support everyday life activities such as meeting friends, shopping, obtaining health information, etc. In this paper, we report a study with 38 older participants engaging with 3D and non-3D virtual grocery stores in order to identify key factors which affected their experience and satisfaction in social engagement within the virtual environment. A mixed method of questionnaire and contextual interview were used for data collection and analysis. We present some preliminary finding within the scope of this position paper, focusing on various aspects of virtual world such as avatars, non-verbal communication cues, etc.
Keywords: 3D virtual games